HUBUNGAN SIKAP DUDUK DAN LAMA DUDUK DENGAN LOW BACK PAIN - Miliantara, Haliya Nida (Jurnal MedScientiae, 2026)
LBP (Low Back Pain) represents a significant ergonomic problem with economic consequences due to decreased worker productivity. Previous studies have shown inconsistent results regarding the relationship between sitting posture and sitting duration with LBP incidence. Objective: This study aimed to analyze the relationship between sitting posture and sitting duration with LBP incidence among employees of the Social Services Department of DKI Jakarta Province. Methods: This descriptive analytic study with cross-sectional approach involved 39 employees selected using consecutive sampling technique. Data collection utilized the Roland-Morris Disability Questionnaire (RMDQ) to measure LBP and RULA (Rapid Upper Limb Assessment) to evaluate sitting posture ergonomics. Data analysis employed Pearson Chi-Square test. Results: The majority of respondents experienced LBP (61.5%), with 41% having low-risk sitting postures and 54.1% with prolonged sitting duration. Bivariate analysis showed significant relationships between sitting posture and LBP (p=0.000) and sitting duration and LBP (p=0.000). Among respondents experiencing LBP, 87.5% had moderate-high risk sitting postures and 95.8% had prolonged sitting duration. Conclusion: There is a significant relationship between sitting posture and sitting duration with LBP incidence among employees. Ergonomic education, workplace environment modifications, and regular stretching programs are recommended to prevent and reduce LBP incidence among office workers.